Speech console - SS, Murthy; N, Rathna (Journal of All India Institute of Speech and Hearing)
Speech and Hearing professionals require many electronic equipments for diagnostic and therapeutic purposes. Any speech therapist practicing in a clinic require at least a few instruments like Speech Trainer, Noise Aversion Apparatus, Shock Aversion Apparatus, Click Aversion Apparatus, Loop Induction System etc. At present as this field is not well developed in our country, the above said instruments are not available in the market. For a newly practicing professional to have all these equipments at a time would be very expensive and sometimes impossible to obtain for various reasons. Alternatively if there is a single instrument available which provides all the above said facilities it will be easier for anybody to procure and use in the profession.